2014
DOI: 10.1007/978-3-319-05579-4_45
|View full text |Cite
|
Sign up to set email alerts
|

Big Data-Driven Marketing: How Machine Learning Outperforms Marketers’ Gut-Feeling

Abstract: Abstract. This paper shows how big data can be experimentally used at large scale for marketing purposes at a mobile network operator. We present results from a large-scale experiment in a MNO in Asia where we use machine learning to segment customers for text-based marketing. This leads to conversion rates far superior to the current best marketing practices within MNOs.Using metadata and social network analysis, we created new metrics to identify customers that are the most likely to convert into mobile inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 12 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…Assunção et al [7] propose that Big Data analysis is the key to enterprises gaining competitive advantage by helping them understand consumer behavior, segment customer groups, provide customized services, and gain more potential customers. The experimental study of Sundsøy et al [8] confirms that in mobile network marketing, operators use Big Data-driven methods to segment customers and achieve accurate marketing, which improves the conversion rates of potential customers. Enterprises can therefore identify these consumers and then increase consumer conversion rates through Big Data marketing, which in turn increases product sales.…”
Section: Introductionmentioning
confidence: 90%
“…Assunção et al [7] propose that Big Data analysis is the key to enterprises gaining competitive advantage by helping them understand consumer behavior, segment customer groups, provide customized services, and gain more potential customers. The experimental study of Sundsøy et al [8] confirms that in mobile network marketing, operators use Big Data-driven methods to segment customers and achieve accurate marketing, which improves the conversion rates of potential customers. Enterprises can therefore identify these consumers and then increase consumer conversion rates through Big Data marketing, which in turn increases product sales.…”
Section: Introductionmentioning
confidence: 90%
“…Numerous studies demonstrated that a key way to increase the effectiveness of DM strategies is the application of DS techniques in this industry ( Braverman, 2015 , Dremel et al, 2020 , Sundsøy et al, 2014 ). For example, Kelleher and Tierney (2018) argued that DS can increase the effectiveness of DM by improving issues such as (i) companies’ management of the information collected from users; (ii) the type and source of data from the companies’ datasets, and (iii) application of new data analysis and innovative techniques to create knowledge ( Palacios-Marqués et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ensemble methods have been proven as powerful algorithms when applied to large-scale telecom datasets [14] [6]. They combine predictions of several base classifiers built with a given learning algorithm in order to improve robustness over a single classifier.…”
Section: B Modelsmentioning
confidence: 99%
“…Recent advances in Deep Learning [1] [2] have made it possible to extract high-level features from raw sensory data, leading to breakthroughs in computer vision [9][10] [11] and speech recognition [12] [13]. It seems natural to ask whether similar techniques could also be beneficial for useful prediction tasks on mobile phone data, where classic machine learning algorithms are often under-utilized due to time-consuming country and domain-specific feature engineering [6].…”
Section: Introductionmentioning
confidence: 99%